2021
DOI: 10.1021/acs.jpcc.1c05502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pore Surface Chemistry on the Rotational Dynamics of Nanoconfined Water

Abstract: We have investigated the dynamics of water confined in mesostructured porous silicas (SBA-15, MCM-41) and four periodic mesoporous organosilicas (PMOs) by dielectric relaxation spectroscopy. The influence of water−surface interaction has been controlled by the carefully designed surface chemistry of PMOs that involved organic bridges connecting silica moieties with different repetition lengths, hydrophilicity, and H-bonding capability. Relaxation processes attributed to the rotational motions of nonfreezable w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…40 Due to confinement effects, crystallization started below −40 °C in water-filled matrices, in agreement with previous dielectric spectroscopy and DSC studies. 24,25 Compared to bulk ice, the spectra of water-filled matrices measured below the freezing point, e.g., at T = −100 °C (cf. right bottom panel in Figure S1) present a blue-shifted excess of spectral intensity above 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…40 Due to confinement effects, crystallization started below −40 °C in water-filled matrices, in agreement with previous dielectric spectroscopy and DSC studies. 24,25 Compared to bulk ice, the spectra of water-filled matrices measured below the freezing point, e.g., at T = −100 °C (cf. right bottom panel in Figure S1) present a blue-shifted excess of spectral intensity above 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that in confinement, ice is defective and coexists with amorphous regions, in agreement with previous studies indicating the existence of an unfreezable interfacial layer. 25 In the present study focusing on the structure of the liquid state, we restricted the spectral analysis to temperatures above −15 and −40 °C for the bulk and capillary filled samples, respectively. The corresponding spectra are presented in Figure 3a for water-filled MCM-41.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During such a short time, we believe that most of water molecules can stay the same subregion as the initial time. Furthermore, rotational properties of confined water have been studied by various experimental techniques such as dielectric relaxation spectroscopy (DRS), 82 nuclear magnetic resonance (NMR), 83 and quasielastic neutron scattering (QENS). 84 Recent 2 H NMR results by Kyakuno et al 83 have reported that the rotational correlation time of water in CNTs is about 10−20 ps, which is well comparable with our calculation results in Figure 8.…”
Section: ■ Results and Discussionmentioning
confidence: 99%